PERANCANGAN SISTEM INFORMASI AKUNTANSI LAPORAN KEUANGAN (STUDI KASUS PADA PT. 212 SIAGA PROPERTY MANAGEMENT) - Ony Widilestariningtyas; Dwi Rahayu Boedikartini; Rio Yunanto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
212 Siaga Property Management make a move area of service of security. When the writer research at financial administration, they making of financial statement still use the Microsoft Office Excel as a means of calculate. For the problems hence writer take the title "Desaign of Accounting Information Systems Financial Statement (Cases Study at PT. 212 Siaga Property Management with Microsoft Visual Basic 6.0 and SQL Server 2000 Bases of Client Server." Research design which writer applies research design with data primer/secunder, research type which writer applies basic and administer research, data type that writer use qualitative data and quantitative data, research method that writer use survey and descriptive research, data collecting technique that writer use field study consisted of by interview, observation and literature study, system development method that writer use methodology orienting at process, data and output. System development structure that writer use waterfall. After writer make the device of information system of financial statement accountancy, expected in processing of transaction and making of financial statement at PT. 212 Siaga Property Management become computerized better according to standard of financial accounting and output yielded is Financial Statement Balance, Balance, Cash Flow, and Capital Change.